A Study on Minimal Cyclic Codes of Length pnq: Exploring the properties of minimal cyclic codes of length pnq (Journal of Advances and Scholarly Researches in Allied Education, 2014)
We aim at the circle R_(pn q) = GF (l)[x](x(pn q)-1), If p, q, are separate odd primes, both pn and q are a primitive root.. Explicit terminology for the entire (d+1)n+2 Early idempotents are acquired, d=gcd(ϕ(q)),p∤(q-1) Dimensions and distances created by polynomials are discussed as well as minimum cyclic length codes pnq over GF(l).